2012
DOI: 10.1002/jcu.21874
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian and pulmonary artery steal phenomenon in a patient with isolated left subclavian artery and right aortic arch

Abstract: We describe a patient with an isolated left subclavian artery associated with right aortic arch, patent ductus arteriosus, and ventricular septal defect. As the isolated left subclavian artery is supplied by the left vertebral artery in which blood flows in the retrograde direction, this anomaly is usually responsible for a congenital subclavian steal phenomenon. Atrophy of the left cerebral hemisphere and inverted left vertebral arterial flow were clearly depicted by echoencephalography in this patient, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The surgical decision to reconnect the RSCA to the aortic arch, as done in our case, may be preventive for subclavian steal syndrome on the long run, as described in one case with D-TGA and isolated RSCA [ 2 ] or more frequently in other CHD with isolated LSCA [ 6 ]. Equally leaving the RSCA would account for the pulmonary steal phenomenon as soon as the pulmonary pressure and resistance normalize after arterial switch operation.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical decision to reconnect the RSCA to the aortic arch, as done in our case, may be preventive for subclavian steal syndrome on the long run, as described in one case with D-TGA and isolated RSCA [ 2 ] or more frequently in other CHD with isolated LSCA [ 6 ]. Equally leaving the RSCA would account for the pulmonary steal phenomenon as soon as the pulmonary pressure and resistance normalize after arterial switch operation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tetralogy of Fallot with a right-sided aorta should prompt the diagnostician to analyze the direction and the nature of flow in the left subclavian artery. Medical history and clinical examination indicative of reduced pulse in the left radial artery, headache, and impaired vision (due to the steal syndrome) help make a correct diagnosis (10,11) . It should be emphasized that the topographic proximity between LCCA and LSA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the left subclavian artery usually presents with no apparent symptoms in neonates, but it may present with congenital pulmonary steal syndrome, subclavian steal syndrome, or may even present in adults with late symptoms due to sporadic progression. Hayabuchi et al [ 6 ] reported the case of a three-month-old girl with cerebral atrophy and an underdeveloped left arm. Jesudian et al [ 7 ] reported the case of a 15-year-old boy with an underdeveloped left arm.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that adequate collateral circulation must be ensured, meaning that reconstruction of the isolated subclavian artery is optional, regardless of the symptoms and signs. Successful results have been reported after ligation or device closure of the PDA and ligation of the left subclavian artery [ 1 , 6 ]. However, reconstruction of the left subclavian artery due to pulmonary steal syndrome after right PDA closure in bilateral PDA has been reported.…”
Section: Discussionmentioning
confidence: 99%